2016
DOI: 10.1177/0142723716673958
|View full text |Cite
|
Sign up to set email alerts
|

Morphosyntactic development of Bangla-speaking preschool children

Abstract: Access to the full text of the published version may require a subscription. Rights Stephanie Stokes and Thomas KleeThe University of Hong Kong, Hong Kong Paul FletcherUniversity College Cork, Ireland AbstractThis study examines the morphosyntactic development, specifically verb morphology, of typically-developing Bangla-speaking children between the ages of two and four. Three verb forms were studied: the Present Simple, the Present Progressive, and the Past Progressive.The study was motivated by the observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…As expected, performance of the children with LD on the three target verb forms, in comparison with the TD group's scores on the same tasks (Sultana et al 2016), revealed significantly lower scores across all forms (figure 3), which was confirmed by one-way ANOVAs. The differences in performance between the two groups are consistent with cross-linguistic findings on LD that have revealed that children with language difficulties perform poorly on a range of morphosyntactic measures compared with older TD children (e.g., Acarlar and Johnston 2011, on Turkish, Fletcher et al 2005, on Cantonese, Leonard et al 2004, on English and Swedish, Lukács et al 2009.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…As expected, performance of the children with LD on the three target verb forms, in comparison with the TD group's scores on the same tasks (Sultana et al 2016), revealed significantly lower scores across all forms (figure 3), which was confirmed by one-way ANOVAs. The differences in performance between the two groups are consistent with cross-linguistic findings on LD that have revealed that children with language difficulties perform poorly on a range of morphosyntactic measures compared with older TD children (e.g., Acarlar and Johnston 2011, on Turkish, Fletcher et al 2005, on Cantonese, Leonard et al 2004, on English and Swedish, Lukács et al 2009.…”
Section: Discussionsupporting
confidence: 76%
“…(Values for the TD group in these analyses come from the performance of a group of Bangla-speaking TD children on the same tasks, as reported in Sultana et al 2016.) (Values for the TD group in these analyses come from the performance of a group of Bangla-speaking TD children on the same tasks, as reported in Sultana et al 2016.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations